E-041 Endovascular Treatment of Intracranial Aneurysms with Barricade Coils: Safety and Efficacy in a Prospective Series. (29th July 2016) - Pierot, L; Zidan, M; Foussier, C; Metaxas, G; Soize, S
Abstract : Purpose: The superiority of endovascular treatment versus surgery in the management of intracranial aneurysms was initially demonstrated in ISAT, endovascular treatment being performed using bare platinum coils. Despite the appearance of new endovascular techniques (stenting, flow diversion, flow disruption), coiling still is the first-line treatment singularly for ruptured aneurysms. New coils are usually not evaluated except if they are surface-modified. However as new bare coils have also different characteristics, it is important to evaluate their safety and efficacy. Materials and methods: Patients with intracranial aneurysms treated between October 2013 and December 2015 in Reims University Hospital by simple coiling or balloon-assisted coiling with Barricade Coils (Blockade Medical, Irvine, California, USA) were prospectively included in a database and retrospectively studied. Patients treated with other devices (stents, flow diverters, flow disrupters) were not included in these series. For all included patients, medical charts, imaging studies and initial and follow-up imaging examinations were reviewed by an independent practitioner that made a comprehensive evaluation of the procedural and post-procedural complications, morbidity and mortality rates, one month clinical follow-up, and anatomical results. Results: From October 2013 to December 2015, 98 patients having 110 saccular intracranial aneurysms were treated with Barricade coils (Blockade Medical, Irvine, California, USA). Ten patients with 13 aneurysms adjunctive devices and were excluded. Finally 88 patients (59 females, 67.1% and 29 males, 32.9%) aged 30 to 83 years (mean: 52 ± 13 years) with 97 aneurysms (57 ruptured, 58.7% and 40 unruptured, 41.3%) were included. Aneurysm locations were internal carotid artery (36 aneurysms, 30.9%), anterior communicating and anterior cerebral arteries (31 aneurysms, 31.9%), middle cerebral artery (16 aneurysms, 16.5%), vertebrobasilar system (14 aneurysms, 14.4%). Seventy-seven aneurysms (79.4%) were treated with simple coiling and 20 (20.6%) with balloon-assisted coiling. Aneurysm coiling was feasible in all aneurysms. Thromboembolic events with or without clinical worsening were encountered in 14/97 procedures (14.4%) intraoperative rupture in 6 aneurysms (6.6%), all without clinical worsening. Overall the procedural morbidity and mortality were encountered in 2 patients (2.1%) and 1 patient (1.0%), respectively. Post-operative anatomical results were complete aneurysm occlusion in 79 aneurysms (81.4%), neck remnant in 13 aneurysms (13.4%) and aneurysm remnant in 5 aneurysms (5.2%). Conclusion: Preliminary results in this prospective series show good safety and efficacy of Barricade coils in aneurysm treatment. Disclosures: L. Pierot: 2; C; Blockade. M. Zidan: None. C. Foussier: None. G. Metaxas: None. S. Soize: None.